Supporting Entrepreneurship and Innovation in Higher Education in Hungary (OECD Skills Studies, 2017)
This report presents evidence-based analysis of current strategies and practices in higher education institutions (HEIs) in Hungary towards a value-creating use of knowledge resources for innovation and entrepreneurship. The analysis and recommendations are highly relevant for policy makers and HEI leaders in other countries. Increased attention to innovation and entrepreneurship both from public policy actors and HEI leadership has triggered an incremental change process in the organisational culture of HEIs and a new approach to education and research for students and staff. HEInnovate is a joint initiative of the European Commission and the OECD to promote the innovative and entrepreneurial higher education institution across Europe and beyond (www.heinnovate.eu)